Diversity and Distribution of Avifauna of Lakkavalli Range Forest, Bhadra Wildlife Sanctuary, Western Ghat, India - Harisha, M. N.; Hosetti, B. B. (Ecoprint: An International Journal of Ecology, 2010)
A total of 132 species of birds belonging to 34 families under 11 orders were recorded during the study period between April 2007 to March 2008 in the Lakkavalli range forest, Bhadra Wildlife Sanctuary, Western Ghat, Karnataka, India. There were 112 resident, 12 winter migratory, 7 local migratory and one summer migratory birds, respectively. Among the birds recorded in the study area, about 49% were insectivores and other dominating types included mixed diet 25%, omnivores 11% carnivores 9%, granivores 3% and frugivores 3%, respectively. Species richness was maximum in the early winter and relatively less in other seasons. Key words: Western Ghat, Lakkavalli, avifauna diversity, landscape. DOI: 10.3126/eco.v16i0.3469 ECOPRINT 16: 21-27, 2009